Perlindungan Hukum Terhadap Data Pribadi Pemilik Identitas Kependudukan Digital - Rizky Dwi Priyantiwi; Hufron (JUSTITIA JURNAL HUKUM, 2025)
Personal data is a person's privacy right that must be protected from various aspects of life. Many people are deceived regarding falsified electronic ID cards, both data falsification and falsification using other people's data. The state is obliged based on its constitutional rights to provide legal protection for various aspects of the lives of Indonesian citizens. The purpose of this study is to determine and analyze the urgency of legal protection for personal data of digital population identity owners as a privacy right in Indonesia and to determine and analyze the concept of legal protection for personal data of digital population identity owners as a privacy right in Indonesia. This type of research is normative legal research. The results of the study obtained that the urgency of legal protection for personal data of digital population identity owners (Digital ID Cards) includes protecting privacy rights and human rights, preventing misuse of personal data, building a safe and trusted digital ecosystem, impacts on social life and diversity, and ensuring legal certainty. The concept of legal protection for digital population identity holders (Digital ID Cards) is by implementing Law Number 11 of 2020 concerning Electronic Information and Transactions (ITE Law), Regulation of the Minister of Communication and Information Technology Number 20 of 2016 concerning Personal Data Protection in Electronic Systems, regulation of personal data protection in sectors, supervision and sanctions, public awareness campaigns, development of data security frameworks, and international cooperation.